2019
DOI: 10.1103/physrevb.100.054409
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of structure and magnetism across the metal-insulator transition in the pyrochlore iridate (Nd1xCax)2Ir

Abstract: We report on the evolution of the thermal metal-insulator transition in polycrystalline samples of Nd2Ir2O7 upon hole-doping via substitution of Ca 2+ for Nd 3+ . Ca substitution mediates a fillingcontrolled Mott-like transition with minimal resolvable structural changes and without altering site symmetry. Local structure confirms that Ca substitution does not result in local chemical phase separation, and absorption spectroscopy establishes that Ir cations maintain a spin-orbit entangled electronic configurat… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 48 publications
(63 reference statements)
1
9
0
Order By: Relevance
“…That the measured Ir moment is consistent with other pyrochlore iridates with non-magnetic A-sites (A = Y, Lu) points to a common basis for the Ir XMCD signal. We also note that a parallel XMCD measurement on Nd2Ir2O7 yielded a very similar value [18]. The source of this signal remains an open question, and XMCD measurements of the remanence (i.e.…”
Section: Discussionsupporting
confidence: 58%
See 3 more Smart Citations
“…That the measured Ir moment is consistent with other pyrochlore iridates with non-magnetic A-sites (A = Y, Lu) points to a common basis for the Ir XMCD signal. We also note that a parallel XMCD measurement on Nd2Ir2O7 yielded a very similar value [18]. The source of this signal remains an open question, and XMCD measurements of the remanence (i.e.…”
Section: Discussionsupporting
confidence: 58%
“…Calculations based on application of the sum rules reveal a small Ir moment of ≈ .005 µB/Ir. Details on this calculation and estimation of the <TZ> term can be found in Porter et al [18]. A previous measurement for Sr2IrO4, which also contains Ir 4+ in a cubic CEF environment, showed a L3 XMCD signal of 3%, with a corresponding net moment of ≈ .05 µB/Ir in the weakly ferromagnetic state [40].…”
Section: Xas and Xmcdmentioning
confidence: 99%
See 2 more Smart Citations
“…Similar to other strongly correlated systems, a direct route to investigating the evolution of the quantum phases in pyrochlore iridates is by chemical substitution. Several such studies have already been reported, for example, in Bi doped Eu 2 Ir 2 O 7 17 ; chemical doping of Ca 2+ for Nd 3+ in Nd 2 Ir 2 O 7 18 , etc. In PIO, the local moment comes from Pr 3+ ion and conduction electrons are mainly contributed by Ir 4+11,19 .…”
mentioning
confidence: 98%